Methods and Approaches to Using Web Archives in Computational Communication Research. Issue 2 (3rd April 2018) - Weber, Matthew S.
ABSTRACT: This article examines the role of web archives as a critical source of data for conducting computational communication research. Web archives are large-scale databases containing comprehensive records of websites showing how those websites have evolved over time. Recent communication scholarship using web archives is reviewed, demonstrating the breadth of research conducted in this space. Subsequently, a methodological framework is proposed for using web archives in computational communication research. As a source of data, web archives present a number of methodological challenges, particularly with regards to the accuracy and completeness of web archives. These problems are addressed in order to better inform future work in this area. The closing sections outline a forward-looking trajectory for computational communication research using web archives.